Harmony in Paradox: Unveiling Jalāl al-Dīn al-Rūmī’s Universalism and Its Impact on Contemporary Islamic Thought - Md Amin, Mohamed Eusuff (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
Abstract: The universalism of Jalāl al-Dīn al-Rūmī is widely celebrated not only by Muslims who are liberal and modern but also by followers of other belief systems even those who have a secular outlook on life and the world. Because of the appeal of this “universalism”, in relation to some contemporary views of Islam (which are not necessarily true), Rūmī is viewed as “unorthodox”, “blasphemous” and “infidel”. On the other hand, to another large fraction of the Muslim population, Rūmī is a true Muslim, and his teachings are essential to spiritualize the contemporary experience of Islam after the religion itself is reduced to legal matters due to the assault of modernity moulded from the secular outlook of the world. This article wishes to resolve this ignorant paradox. Through the method of logical reasoning, this paper will refer to sayings attributed to Rumi and step by step establish the universalism aspect of Islam in Rumi’s thought. This paper, through Rūmī’s legacy, shows (i) the dynamism of Islam as a religion; (ii) how the anxiety of secularism is answered by Islam; and (iii) the perfection of Islam over other forms of beliefs. The conclusion of this paper affirms the said principle with the acknowledgement that the more perfect lover does what the Beloved wishes. At this point, the Quranic distinction between those who have knowledge and those who are ignorant is noted.